PENINGKATKAN KETERAMPILAN SHOOTING SEPAKBOLA MELALUI MODIFIKASI ALAT - Hepi Setiawan (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
This research aims to improve the skills of shooting football throughmodification tool on extracurricular student Malay Kampong SDN 01 PG. Researchmethods the research methods used are action (Action Research) from Taggart andKammis. Subject in this study are students Extracurricular Malay Kampong SDN 01 PGthat add up to 23 students. The instruments used, namely football shooting skills testsassess the process of shooting and movement results shooting soccer. data analysistechniques used are desktiptif qualitative and quantitative increase in percentage form.Soccer shooting skills through modification of the appliance are marked with theincrease of the average student. The average value of the students on the initialconditions of 67 with percentage of success amounting to 30.4%. The conditionexperience an increase in cycle I, namely amounting to 73 and percentage of successamounting to 65.2%. However, the increase is still not reaching the target targets set byresearchers that is 80%. Then researchers continue their action cycle II. Aftercontinuing the cycle II again underwent an increase of 77 with a success percentage of83%. This indicates that the target set previously already accomplished so researchstopped in cycle II. The conclusions of this research are the modifications can improvethe skills of soccer shooting at students extracurricular Malay Kampong SDN 01 PG.Keywords: Action Research, Shooting Soccer, Modification Tools.